2016
DOI: 10.1111/modl.12367
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Weak and Strong Readers in a Foreign Language

Abstract: This study investigated the cognitive (first language [L1] and foreign language [FL]), linguistic (L1 and FL), and motivational characteristics of weak FL readers in contrast to strong readers in 3 groups of L1 Finnish-speaking learners of English, aged 10, 14, and 17 years. This cross-sectional study covered a wide range of potential correlates, and therefore predictors, of FL reading based on previous research on reading in first, second (L2), and foreign languages. The weakest and strongest FL readers (1 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 37 publications
1
40
0
3
Order By: Relevance
“…Despite a possibility of involvement of L1/English‐based processing in L2 Chinese word reading, such a cross‐linguistic influence needs to be treated with caution, as the study did not measure children's English phonological awareness (and other skills in English); thus it is impossible to ascertain any possible (positive) relationship between English phonological awareness and Chinese phonological awareness on the one hand, and with Chinese L2 reading on the other. In addition, whether L1‐based processing is involved or transferred in L2 reading acquisition may also depend on the learning stage or actual proficiency of students and the nature of literacy tasks (e.g., Alderson, Nieminen, & Huhta, ; Yeong, Fletcher, & Bayliss, ). In a study that involved students in the same context as the present study (i.e., Singapore) but that focused on English literacy learning, Yeong and others () found that both Mandarin‐L1 readers of English and English‐L1 readers of English prioritized phonological awareness, as opposed to orthographic processing, in their reading of English words; yet, English spelling of older Mandarin‐L1 readers (11–12 years old) was significantly predicted by orthographic processing as well as phonological awareness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite a possibility of involvement of L1/English‐based processing in L2 Chinese word reading, such a cross‐linguistic influence needs to be treated with caution, as the study did not measure children's English phonological awareness (and other skills in English); thus it is impossible to ascertain any possible (positive) relationship between English phonological awareness and Chinese phonological awareness on the one hand, and with Chinese L2 reading on the other. In addition, whether L1‐based processing is involved or transferred in L2 reading acquisition may also depend on the learning stage or actual proficiency of students and the nature of literacy tasks (e.g., Alderson, Nieminen, & Huhta, ; Yeong, Fletcher, & Bayliss, ). In a study that involved students in the same context as the present study (i.e., Singapore) but that focused on English literacy learning, Yeong and others () found that both Mandarin‐L1 readers of English and English‐L1 readers of English prioritized phonological awareness, as opposed to orthographic processing, in their reading of English words; yet, English spelling of older Mandarin‐L1 readers (11–12 years old) was significantly predicted by orthographic processing as well as phonological awareness.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a possibility of involvement of L1/English-based processing in L2 Chinese word reading, such a cross-linguistic influence needs to be treated with caution, as the study did not measure children's English phonological awareness (and other skills in English); thus it is impossible to ascertain any possible (positive) relationship between English phonological awareness and Chinese phonological awareness on the one hand, and with Chinese L2 reading on the other. In addition, whether L1-based processing is involved or transferred in L2 reading acquisition may also depend on the learning stage or actual proficiency of students and the nature of literacy tasks (e.g., Alderson, Nieminen, & Huhta, 2016;Yeong, Fletcher, & Bayliss, 2014).…”
Section: Phonology In L1 and L2 Chinese Word Readingmentioning
confidence: 99%
“…They also add that regarding being sources of proficiency measurements, those language elements discussed previously are better ability predictors of productive language skills (e.g., writing and speaking) instead of receptive language skills such as listening and reading comprehension. These theories are still valid and thoughtprovoking in recent researches on reading comprehension (e.g., Alderson, Huhta, & Nieminen, 2016;Sparks et al, 2008).…”
Section: Pinpointing Learners' Necessary Linguistic Competencementioning
confidence: 97%
“…Though it is possible to turn the less motivated learners to become more motivated and in the classroom context, the instructors are the ones who can make it. Instructors possess the ability to change learners' attitude toward learning become more positive (Alderson, Huhta, & Nieminen, 2016). The real challenge here is how the teacher can approach learning that directs learners into realising the expectancy and values of the reading material brought into the class.…”
Section: Predicting and Encouraging Learners' Reading Motivationmentioning
confidence: 99%
See 1 more Smart Citation